PENGARUH PEMBAYARAN PAJAK PARKIR MELALUI E-PARKING DALAM MENINGKATKAN OMZET PENDAPATAN ASLI DAERAH KOTA SURABAYA - Monica Gandasari; Junaidi Junaidi; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThe large number of vehicle users who park their vehicles on the side of the road can bring many losses such as increasing the degree of saturation or increasing density due to reducing the capacity of the road to accommodate the volume load of passing vehicles. This study aims to examine the effect of parking tax via electronic (e-parking) on the Regional Original Income (PAD) of Surabaya City during the 2017-2020 period. Meanwhile, the population used data from the Parking-Q company that engaged in parking engineering. The sampling technique used a saturated sampling technique or what is called a census, namely by using all data from the population. This study took 77 samples from all data contained in the population. Technical analysis uses simple regression because it only uses one Keywords: E-parking, Regional Taxes, Local Own Revenue